PERSEPSI MAHASISWA TERHADAP PENGGUNAAN BALIKAN SESAMA PEMELAJAR DALAM KEMAHIRAN MENULIS DI PERGURUAN TINGGI INDONESIA - Audrey Gabriella Titaley; Dwi Imroatu Julaikah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
The current difficulty for Indonesians to be open to criticism and suggestions and to show appreciation for the diversity of opinions further encourages the need for the development of an academic culture in Indonesia, especially in higher education. Efforts to develop open-mindedness need to be carried out and this study suggests using peer feedback in writing classes. This study aimed to examine the perceptions of openness of German learners at the B2 language level towards peer-student feedback in students' writing skills. The findings of this mixed study proved that students were open to feedback from fellow students because they considered and used it in writing improvement. Students were also able to provide feedback that was delivered in a facilitative manner to appreciate the voice of the text writer. The results of the questionnaires distributed showed the students' positive attitude towards the feedback of fellow students and the desire to get this feedback in the future.